Natural and anthropogenic sources of atmospheric pollution: state of the art of its impact on the physicochemical properties of the rain water and fog water - Mora-Barrantes, Jose Carlos (2021)
In this article, a description is presented on the state of the art related with the influence of natural and anthropogenic atmospheric pollutant sources on the physical and chemical properties of the rain water and fog water. It was determined that most of the researches done have been located on urban areas and have evaluated the impact of the anthropogenic emissions to the atmosphere on  water quality. There have been a limited quantity of investigations in forest zones. The few ones point out an important influence of human pollutant emissions on the properties of rain water and fog water. In the particular case of Costa Rica, two prelaminar researches have been done. The literature review on the state of the art suggested the need for longer research periods  in sampling and analyzing  rainwater and fog water, in order to do a better control  of their physicochemical parameters.  Future researches shall study deeply the natural and anthropogenic sources of atmospheric pollutants in the surroundings of the areas of study.